Identification of Distinct Research Gaps that Complement Previous Critiques of Militaristic Language in Relation to Cancer and Other Non-Military Topics - Kari Almendingen PhD (Cancer Control)
Militaristic language is pervasive in cancer discourse across media, fundraising, politics, healthcare, and science, despite longstanding critiques from both civilian and military perspectives. Critics argue that framing cancer as a war or battle can lead to feelings of shame and inadequacy, particularly for those with metastatic cancer. This language often diverts focus from prevention and early detection strategies, complicating public perception and understanding of cancer. Two distinct research gaps related to the use of militaristic language in cancer discourse remain unaddressed: the role of dual-use technologies and the perspectives of individuals with wartime experience. Dual-use technologies, initially developed for military applications, have significantly advanced cancer diagnosis and treatment. Yet, their historical and ethical implications are largely absent from public discourse and scientific literature. Awareness of the complex role that dual-use technologies play in cancer diagnostics and treatment, as well as in other societal areas, could influence the prevalence of militaristic language used to describe challenges like cancer, drugs, poverty, and other civil issues. Secondly, studies have not examined opinions on the use of militaristic language among individuals with firsthand wartime experience, — such as civilian victims, military personnel, veterans, pacifists, and aid workers — compared to those without such experience. Both of these omissions may skew findings and overlook diverse perceptions. Addressing these research gaps could foster a more respectful public cancer discourse that takes into account the experiences of affected individuals. This commentary expands on existing critiques, urging professionals to adopt nuanced and inclusive language for cancer and other peaceful topics. Militaristic language is outdated, ethically questionable, and should not be used in science, healthcare, politics, fundraising, or other public contexts.